Manuscript of Mushaf Al-Qur'an K.H. Muhammad Ihsan Wonodoyo Gunungkidul (Codicology-Textology Aspect Analysis) - Khairun Niam; Tatsa Alifah (Journal of Islamic History and Manuscript, 2023)
This article examines K.H. Muhammad Ihsan's Qur'an manuscript is located in Wonodoyo Hamlet, Gunungkidul Regency, Yogyakarta.   Mr. Jazari Zaeni keeps this privately owned manuscript as the heir of the manuscript. This research focuses on the characteristics of the mushaf. The approaches used are codicology and textology as an analysis tool. The codicological aspect includes the size and material of the manuscript, illumination, and the symbols in it. Meanwhile, textological studies refer to the use of rasm, qira'at, and punctuation. The results of this study found that the size of the mushaf is 32 x 21 cm with a thickness of 7 cm. The illumination in this manuscript is geometric type with square and triangle lines. In textology, this manuscript has distinctive characteristics, namely the writing of verses using mixed rasm, the qira'at of Imam 'Ashim narrated by Hafs, and punctuation marks that are still relatively simple and do not escape text correction. In addition, there is no colophon or information related to copying.